Pengaruh Live Streaming, Celebrity Endorsements dan Online Customer Reviews terhadap Perilaku Impulsive Buying Gen Z dengan Kepercayaan Konsumen sebagai Variable Intervening di Kecamatan Medan Helvetia (Studi Kasus Tiktok Shop) - Trissa, Yovanda Audiva; Salqaura, Siti Alhamra; Siregar, Muhammad Yamin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of live streaming, celebrity endorsements, and online customer reviews on impulsive buying behavior of Gen Z with consumer trust as an intervening variable in Medan Helvetia District (TikTok Shop Case Study). The research used a quantitative approach that will find the magnitude of the influence of the independent variable on the dependent variable. The population in this study is Gen Z in Medan Helvetia District who made purchases through TikTok Shop, the number of which is unknown. Because the population size is not known with certainty, the Lemeshow formula was used to determine the sample with a 95% confidence level and a 10% sampling error, resulting in a sample of 96 respondents. Data analysis used SmartPLS (Partial Least Square) starting from the measurement model (outer model), model structure (inner model) and hypothesis testing. The results showed that live streaming, celebrity endorsements, and online customer reviews have a positive and significant effect on consumer trust in Gen Z in Medan Helvetia District. These three variables also have a positive and significant effect on impulsive buying behavior. Consumer trust is proven to have a positive and significant effect on impulsive buying behavior. Indirectly, live streaming, celebrity endorsements, and online customer reviews have a positive and significant influence on impulsive buying behavior through consumer trust among Gen Z in Medan Helvetia District.